Pasando por comadrona, midwife y médico: el itinerario terapéutico de una embarazada en Guatemala - Fleischer, Soraya (2006)
In this article, I discuss, according to the theoretical-analytical framework of Menéndez (1994), how women and their midwives follow a plural therapeutical itinerary during pregnancy and labor in the region of Antigua, Guatemala. I look forward to present and analyze an example of a delivery that happened during my research, first, as a paradigmatic example of dialogue, not always friendly and pacific, among various local medical systems: a Mayan comadrona (the local midwife), a ladino doctor and a foreign nurse-midwife. Second, this delivery illustrates an encounter that brings together ethnic, class, and gender relations influences by power and conflict that has structured the material and symbolic construction of this "young" country.